Tinjauan Analisis Desain Formulir Ringkasan Pulang Rawat Inap di RSUD Kabupaten Bekasi Tahun 2022 - Anggita Nurul Fadlilah; Wiwik Viatiningsih; Puteri Fannya; Nanda Aula Rumana (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
Medical record form is a design tool with a predetermined filling limit to be used as one of the media. Inpatient discharge summary form is a brief record of the patient's condition during inpatient treatment. The purpose of this study was to determine the analysis of the inpatient discharge summary form design at the Bekasi District Hospital 2022. This study used a qualitative descriptive research method by re-examining the data that had been obtained in order to obtain valid data and classifying the data that had been obtained by entering it into a data table. then redesigned the form as a suggestion for the Bekasi District Hospital. Based on the data analysis that has been carried out, it is concluded that the Bekasi District Hospital has an SOP for Changes in Form Design which is used as a guide for any form design changes in the Bekasi District Hospital which has been determined by the Director of the Bekasi District Hospital on December 27, 2017. The results of the analysis carried out on Inpatient discharge summary form on physical, anatomical and content aspects shows that the paper used is still using NCR 55 gsm, the title of the form is still using an Inpatient Medical Resume not using the title of the Inpatient Discharge Summary form, on the form there is no edition number and page number, no there are instructions in filling out the form, there are unusual abbreviations such as ICD-9 CM and ICD-10 CM and there is a